2015
DOI: 10.1002/lno.10029
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic hydrologic and biogeochemical processes drive microbially enhanced iron and sulfur cycling within the intertidal mixing zone of a beach aquifer

Abstract: Intertidal aquifers host a reactive zone comprised of Fe mineral‐coated sands where fresh and saline groundwaters mix. This zone may significantly influence the export of C, N, P, Fe, and other metals in submarine groundwater discharge (SGD). Toward determining the roles of microbes in Fe and S mineralization, and the interplay of microbiology with geochemistry and physical hydrology, we conducted a biogeochemical study of pore waters at Cape Shores, Delaware. Here, fresh groundwater provides Fe(II), which pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 62 publications
(86 reference statements)
4
105
0
Order By: Relevance
“…It is known that microaerophilic Fe(II) oxidizers can reach numbers of up to 10 7 cells/ml in iron-rich marine environments, such as Fe(II)-containing hydrothermal vents (36,37). While Gallionella, Sideroxydans, and Leptothrix seem to be restricted to limnic and terrestrial habitats, the genus Mariprofundus may be restricted to marine habitats (38)(39)(40)(41)(42). Information about the presence of photoferrotrophs in marine sediments is scarce, and there are only two isolates, Rhodovulum iodosum and Rhodovulum robiginosum, which were both isolated from a tidal mud flat in the German Wadden Sea (43,44).…”
mentioning
confidence: 99%
“…It is known that microaerophilic Fe(II) oxidizers can reach numbers of up to 10 7 cells/ml in iron-rich marine environments, such as Fe(II)-containing hydrothermal vents (36,37). While Gallionella, Sideroxydans, and Leptothrix seem to be restricted to limnic and terrestrial habitats, the genus Mariprofundus may be restricted to marine habitats (38)(39)(40)(41)(42). Information about the presence of photoferrotrophs in marine sediments is scarce, and there are only two isolates, Rhodovulum iodosum and Rhodovulum robiginosum, which were both isolated from a tidal mud flat in the German Wadden Sea (43,44).…”
mentioning
confidence: 99%
“…3). Thus, the USP at Spiekeroog beach may extend down to greater depths than previously shown in other studies using salinity measurements and/or hydrological modeling (Charette and Sholkovitz, 2006;McAllister et al, 2015;Santos et al, 2008;Ullman et al, 2003). The majority of these studies were, however, carried out in microtidal environments, which may explain why the USP does not reach depths exceeding 5 m.…”
Section: Beach Hydrology and Salinity Gradients Influence The Beach Ementioning
confidence: 84%
“…This will lead to a refined groundwater flow model, to a better understanding of the key processes in biogeochemistry, of the role of organisms for OM degradation, and of the fluxes at the sediment-water interface. To date, most studies on hydrological and biogeochemical processes in subterranean estuaries of beach systems were carried out in microtidal and/or low-energy environments such as semi-protected bay situations (Charette and Sholkovitz, 2006;McAllister et al, 2015;Santos et al, 2008;Ullman et al, 2003). Therefore, a maximum sampling depth of about 5 m was sufficient to resolve the USP at these study sites.…”
Section: Perspectivesmentioning
confidence: 99%
“…However, complete gene sets encoding the full denitrification pathway could not be detected. Another recent study found strong correlations between the occurrence of candidate division OP3 16S rRNA genes and the content of oxidized iron minerals at the discharge zone of an intertidal aquifer, speculating on the possible involvement of some members of this group in iron cycling (McAllister et al, ). The iron‐rich sediments of the Bothnian Sea might thus provide a suitable habitat for members of this group.…”
Section: Resultsmentioning
confidence: 99%